Characterization of the analytic performance of an electrochemical point‐of‐care meter for measuring β‐hydroxybutyrate concentration in blood and plasma from periparturient dairy cattle. (9th May 2017) - Megahed, Ameer A.; Hiew, Mark W. H.; Townsend, Jonathan R.; Constable, Peter D.
Abstract : Background: The Precision Xtra electrochemical meter is widely used to measure blood β‐hydroxybutyrate concentration (BHBb) in dairy cattle. The meter uses an algorithm optimized for human blood that assumes the HCT in cattle is the same as in people, and that intra‐erythrocyte β‐hydroxybutyrate (BHBe) and plasma β‐hydroxybutyrate (BHBp) concentration are equivalent. Objectives: The first objective was to characterize the analytic performance of the meter for measuring BHBb and BHBp in dairy cattle. The second objective was to characterize the influence of HCT and sample temperature on BHBp concentration measured by the meter. Methods: Blood and plasma samples were obtained from 106 periparturient Holstein cattle and 15 lactating Holstein cows with experimentally induced electrolyte and acid–base imbalances. Meter performance was evaluated using Deming regression and Bland–Altman plots. Multivariable linear regression was used to determine the effect of HCT and sample temperature on BHBb and BHBp concentration, respectively. Results: The meter was linear up to BHB = 3.0 mmol/L as measured by the reference method, equivalent to meter values for BHBb > 4.5 mmol/L and BHBp > 5.2 mmol/L. An increase in HCT resulted in higher BHBb concentration. This result was partially explained by BHBe being much lower than BHBp. Changes in sample temperature caused a linear change in measured BHBp whenever BHBp > 3.0 mmol/L. Conclusions: Meter accuracy was markedly dependent on the BHBe‐to‐BHBp ratio and consequently the HCT. Therefore, the algorithm used by the meter should be revised when applied to bovine blood for improved accuracy.